RNF219 attenuates global mRNA decay through inhibition of CCR4-NOT complex-mediated deadenylation - Poetz, Fabian; Corbo, Joshua; Levdansky, Yevgen; Spiegelhalter, Alexander; Lindner, Doris; Magg, Vera; Lebedeva, Svetlana; Schweiggert, Jörg; Schott, Johanna; Valkov, Eugene; Stoecklin, Georg (Nature Communications, 2021)
The CCR4-NOT complex acts as a central player in the control of mRNA turnover and mediates accelerated mRNA degradation upon HDAC inhibition. Here, we explored acetylation-induced changes in the composition of the CCR4-NOT complex by purification of the endogenously tagged scaffold subunit NOT1 and identified RNF219 as an acetylation-regulated cofactor. We demonstrate that RNF219 is an active RING-type E3 ligase which stably associates with CCR4-NOT via NOT9 through a short linear motif (SLiM) embedded within the C-terminal low-complexity region of RNF219. By using a reconstituted six-subunit human CCR4-NOT complex, we demonstrate that RNF219 inhibits deadenylation through the direct interaction of the α-helical SLiM with the NOT9 module. Transcriptome-wide mRNA half-life measurements reveal that RNF219 attenuates global mRNA turnover in cells, with differential requirement of its RING domain. Our results establish RNF219 as an inhibitor of CCR4-NOT-mediated deadenylation, whose loss upon HDAC inhibition contributes to accelerated mRNA turnover.
Gesehen am 27.09.2022